Double-network modified asphalt and preparation method thereof

Through the dual network modified asphalt of hydrogen bond-DA double bond, the problem that asphalt self-healing materials can only be repaired in one time in the existing technology, the multiple self-healing and mechanical performance improvement have been achieved, and the service life of asphalt has been extended .

CN119242061APending Publication Date: 2025-01-03CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411374409.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing asphalt self-healing materials can only repair the cracks on the road surface once, and most of the studies are based on a single self-healing mechanism, making it difficult to achieve multiple healing and lasting performance. Most of the research methods are single, so they cannot effectively capture the self-healing of asphalt. Real recovery effect.

Method used

The self-healing mechanism can be explored by using hydrogen bond-DA double bonds to prepare the self-healing mechanism under the action of external forces by using force ductile radiator, Fourier infrared spectrum and differential scanning calorimeter. Dual-network modified asphalt with significantly improved tensile strength and length after first self-healing.

Benefits of technology

The multiple self-healing capabilities of asphalt materials are achieved, the service life of asphalt is extended, and the toughness and mechanical properties of asphalt are improved through the coordination of the dual network structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242061A_ABST
    Figure CN119242061A_ABST
Patent Text Reader

Abstract

The invention discloses double-network modified asphalt and a preparation method thereof, which are characterized in that self-healing mechanism research is carried out on the basis of hydrogen bond-DA double bond asphalt, and the self-healing mechanism is ascertained in multiple scales. The method comprises the following steps: firstly, carrying out a blank experiment on dual-network asphalt by adopting a force-measuring ductility instrument to compare mechanical property changes under different double bond contents; secondly, performing hydrogen bond and DA bond crosslinking analysis on the asphalt sample through Fourier infrared spectroscopy to ensure double-bond double-network synthesis; and finally, verifying the rheological property of the dual-network asphalt by using a differential scanning calorimeter. The research result can play a certain guiding role in deeply exploring the self-healing capability of the asphalt material and expanding the application of the asphalt material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of asphalt materials, and in particular relates to a double-network modified asphalt and a preparation method thereof. Background Art

[0002] With the rapid development of the transportation industry, asphalt pavement has been increasingly widely used due to its superior surface smoothness, seamlessness, driving comfort, wear resistance, low vibration, low noise, short construction period, simple maintenance and repair, and suitability for phased construction. Styrene-butadiene-styrene (SBS) modified asphalt is used as a high-viscosity asphalt in the surface layer of highways, accounting for about 80%. However, complex and diverse road damage requires timely maintenance by road workers to restore road performance to avoid causing greater road damage. The huge maintenance mileage and high maintenance costs have put forward higher requirements on road asphalt materials. Excellent road maintenance technology is one of the main problems that need to be solved in the current road materials discipline.

[0003] At present, there are various technologies for restoring deformation of asphalt pavement, including sand-containing fog seal, slurry seal, micro-surfacing, fiber seal, gravel seal and composite seal. When different forms of pavement damage occur on asphalt pavement, the repairs required are also different. When repairing the pavement, it is necessary to isolate the road section, which is time-consuming and labor-intensive, resulting in a huge waste of resources, and these repairs are passive repairs. The longer the service time of the pavement, the more difficult it is to repair. Therefore, the synthesis of polymer materials with active self-healing capabilities has also become a hot topic for scientific researchers. Therefore, under the multiple challenges of pavement damage repair, it is extremely important to study preventive maintenance technology, and the core of preventive maintenance technology is to study and utilize the self-healing ability of asphalt materials.

[0004] 1. Research on self-healing materials:

[0005] At present, there are two main ways to achieve material self-healing. The first is explant self-healing, that is, by encapsulating the repair agent in microcapsules, hollow fibers or microchannels, and compounding them with the polymer matrix during the material preparation process, when the material matrix is ​​damaged, the repair agent is released from the microcapsules, hollow fibers and microchannels, diffuses to the damaged part of the material and bonds the entire material matrix together to achieve the repair of the polymer material. The second is intrinsic self-healing, that is, reversible covalent bonds (such as S-S bonds, Diels-Alder bonds, etc.) or non-covalent bonds (such as hydrogen bonds, metal ligands, electrostatic effects, etc.) are introduced into polymer molecules. When the material is damaged, the broken dynamic chain segments are entangled and diffused at the damaged part and re-form chemical bonds to achieve the repair of the material. Since explant self-healing requires the introduction of a repair agent, once the repair agent is consumed, the repair of the material cannot be repeated. Therefore, the research on intrinsic self-healing materials has received more attention, especially intrinsic self-healing materials that can be repaired under mild conditions such as low temperature and weak stimulation are the focus of research.

[0006] Hydrogen bonds are a type of dynamically reversible non-covalent bond, and their energy is one-tenth of that of covalent bonds. Therefore, hydrogen bonds are easily broken and reorganized, giving materials self-healing properties at room temperature. However, hydrogen bonds usually form relatively weak crosslinks between polymer chains, and the mechanical properties of the prepared materials are slightly poor. It is difficult to meet people's requirements for material self-healing properties by hydrogen bonding alone. The DA (Diels-Alder) reaction, a reaction discovered by Diels-Alder, is a reversible chemical reaction with low side reactions and affected by temperature. Its working principle is an addition cyclization reaction. When a material containing a DA structure is damaged, the DA bonds can be reorganized when a certain temperature is given, thereby achieving self-healing. However, the DA bond is in a rigid structural region, and its mobility is limited, making it difficult for functional groups to contact each other during repair.

[0007] Liu used the prepolymerization method to prepare two series of UV-curable self-healing polyurethane (PU) oligomers and prepared UV-curable self-healing polyurethane coatings; their structures were characterized by nuclear magnetic resonance spectroscopy and Fourier transform infrared spectroscopy; the results showed that the coating had self-healing properties based on hydrogen bonds, and as the molecular weight of polycarbonate diol decreased, the hardness, tensile strength and glass transition temperature of the coating increased.

[0008] Leibler et al. reported a supramolecular elastomer constructed by hydrogen bond cross-linking with self-healing and thermally reversible properties. When this supramolecular elastomer is damaged or cut, it does not require external stimulation such as heating or catalysts. It can automatically heal itself in a few minutes at room temperature by simply squeezing the broken edges together. This self-healing can be repeated many times, but this repair requires that the broken surfaces be overlapped together in a short time (5 minutes) after the material breaks. If the repair time is too late, the repair efficiency will be reduced or even impossible to repair.

[0009] Liu Yang et al. conducted infrared analysis on the cross-linked polyamide amine and showed that the cross-linked polyamide amine contains abundant hydrogen bonding interactions, indicating that the prepared cross-linked polyamide amine can repair the material through hydrogen bonding and physical interactions, and has potential applications in drug sustained release and other aspects.

[0010] Liu designed a new type of UV-curable self-healing oligomer based on the quadrupolar hydrogen bonding system and identified its structure; the results showed that the reversibility of the quadrupolar hydrogen bonding system is conducive to the improvement of the repair ability.

[0011] Guan's research group introduced hydrogen bonds into the self-healing system based on olefin metathesis reaction and found that hydrogen bonds as sacrificial bonds can greatly improve the elasticity of the material.

[0012] Fan reported a powerful self-healing polyurethane (PU) elastomer. In order to balance the self-healing ability and mechanical properties, a higher healing efficiency can be achieved when the reversibility of hydrogen bonds is unstacking at higher temperatures; the optimized samples have good mechanical properties and healing efficiency.

[0013] For thermal reversibility research, the mainstream method is to conduct material self-healing based on thermal reversible Diels-Alder covalent bonds.

[0014] Sun Lulu and others constructed a Schiff base cross-linked network structure and successfully prepared a self-healing and remodelable thermosetting material. The study showed that the material contained a large number of imine bonds (-C=N-), and a rapid and reversible imine network rearrangement reaction occurred at medium temperature (80-100°C), which made the material exhibit good self-healing and remodeling behavior.

[0015] Wu Meiyin et al. characterized the structure and thermal reversibility of the sample by using nuclear magnetic resonance hydrogen spectrum, attenuated total reflection Fourier transform infrared spectroscopy, differential scanning calorimetry, thermogravimetric analysis and other tests, indicating that it has excellent thermal reversibility. Rheological tests show that the viscosity of the sample drops sharply with increasing temperature and rises sharply with decreasing temperature, and this process can be repeated many times.

[0016] At the same time, some scholars have prepared polyurethane elastomers with self-healing and reprocessable properties by introducing two kinds of dynamic covalent bonds, DA bonds and disulfide bonds, into the main chain and cross-linking points of the polymer. On the one hand, the dynamic bonds distributed in the main chain and cross-linking points enable the polymer molecular chain to achieve self-healing through reversible fracture and recombination. On the other hand, linear molecular chains exist in the cross-linked polyurethane at the same time, thereby improving the mobility of molecules between sections, allowing the damaged sections to quickly infiltrate and improve the repair efficiency.

[0017] Zhang Lunliang, He Xia and others prepared an intrinsic self-healing epoxy resin (EP-DA) containing a thermally reversible DA reaction. The structure and properties of EP-DA were characterized by FTIR, DSC, TGA and electronic universal testing machine. The results showed that after multiple repairs, the repair efficiency was still above 68%.

[0018] In summary, the research found that most scholars use a single self-healing mechanism to study the self-healing of materials. Self-healing elastomers that are cross-linked only by dynamic covalent bonds lack an energy dissipation mechanism, so their toughness is poor; while elastomers that are cross-linked only by supramolecular interactions are prone to creep, stability, and low elasticity. To solve this problem, supramolecular interactions and irreversible covalent bonds are introduced into the elastomer at the same time. When subjected to external force, the supramolecular interaction breaks first to dissipate energy and improve the mechanical properties of the material. It can be seen that the use of dual-network self-healing materials can greatly improve the self-healing efficiency.

[0019] 2. Research on self-healing technology

[0020] The self-healing behavior of asphalt has great potential to promote low-carbon use and extend the service life of asphalt pavement. At present, the self-healing technology of asphalt mixture has also made some progress, mainly microcapsule self-healing technology, which is a real pre-maintenance technology, but the microcapsules used are not entirely sustainable. There is also heat-induced self-healing asphalt mixture technology, and the research results in this area are far richer than those of microcapsule technology. Although this technology can be used multiple times after asphalt fatigue cracking, it also has some disadvantages.

[0021] Wei used a dynamic chemical approach for self-healing of polymer-modified asphalt, and the results showed that it not only avoids long-term cyclic healing caused by externally assisted healing, but also provides potential advantages for polymer-modified materials, including longer service life, reduced repair costs, and improved environmental benefits and sustainability.

[0022] Wang Yuehui et al. studied the self-healing properties of asphalt from a microscopic molecular perspective and studied the effects of crack width and heating temperature on the self-healing properties of asphalt. The results showed that with the increase of crack width, the diffusion coefficient of asphalt gradually decreased and the self-healing rate decreased; with the increase of heating temperature, the diffusion coefficient of asphalt gradually increased and the self-healing rate accelerated.

[0023] He et al. integrated the molecular model of asphalt and healing agent into the microcrack model and used molecular dynamics to simulate the self-healing process of asphalt mixed with healing agent. The results showed that vegetable oil is a better choice to improve the healing rate of virgin asphalt, while aromatic oil is a better choice to improve the healing rate of short-term aged asphalt. The higher the temperature, the better the effect of the healing agent on the asphalt. Virgin asphalt heals above 15°C, and short-term aged asphalt heals the most above 45°C. Molecular simulations show that the healing process depends on the diffusion of healing agents and asphalt into microcracks. After the cracks are filled, asphalt and oil molecules continue to mix. Aromatic oil produces better mixing, resulting in a more uniform composition and better mechanical properties.

[0024] Li et al. used Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy to prove the successful preparation of elastomers containing disulfide bonds / diselenide bonds. The three elastomers were used as modifiers to prepare the corresponding modified asphalt. The results showed that the elastomers containing dynamic disulfide bonds / diselenide bonds have self-healing ability, and the three elastomer modifiers can improve the self-healing ability of asphalt binders.

[0025] Cao introduced disulfide dynamic covalent bonds and amino oxime dynamic covalent bonds into the polyurethane cross-linking structure in asphalt, which provided a new idea for improving the self-healing ability and rheological properties of the binder, reducing the number of pavement maintenance times and extending the service life of the pavement.

[0026] From the above analysis, it can be seen that most experts use macroscopic experiments on asphalt and asphalt mixtures to compare and analyze the performance of specimens before and after healing, and use the mechanical modulus ratio of asphalt materials before and after healing as an evaluation indicator of the healing effect of asphalt materials. However, this only stays at the macroscopic dimension and cannot capture the true recovery effect of asphalt self-healing. The self-healing behavior of asphalt is closely related to the interaction between its internal molecules. Only by analyzing from the microscopic dimension of asphalt molecules can the repair effect of asphalt self-healing be truly analyzed.

[0027] According to the current research status at home and abroad, existing research has achieved fruitful results in the intrinsic self-healing of materials, but there are still some shortcomings and problems to be solved in the self-healing of asphalt materials, which are mainly manifested in the following aspects:

[0028] (1) Existing asphalt self-healing materials can only repair road cracks once, but cannot heal multiple times, which is not conducive to the long-term use of its self-healing effect. Alternatively, the preparation process of materials with multiple repair effects is cumbersome and relatively expensive.

[0029] (2) Most of the existing studies have focused on the intrinsic self-healing repair of polyurethane elastomer materials, but there are relatively few studies on the intrinsic healing mechanism of asphalt materials. Most of them are based on simple stretching-healing-stretching or scanning electron microscopy to observe the self-healing of asphalt over time, and the mechanism research methods are relatively simple. Summary of the invention

[0030] In view of the problems that asphalt self-healing materials in the prior art can only repair road cracks once and cannot heal multiple times, and that most of the asphalt self-healing conditions are observed over time through simple stretching-healing-stretching or scanning electron microscopy, the present invention provides a double-network modified asphalt and a preparation method thereof. The present invention studies the self-healing mechanism of asphalt based on hydrogen bonds-DA double bonds, and explores the self-healing mechanism in multiple scales; firstly, a force ductility meter is used to carry out a blank experiment on the double-network asphalt to compare the changes in mechanical properties under different double bond contents; secondly, the asphalt sample is subjected to hydrogen bond and DA bond cross-linking analysis by Fourier transform infrared spectroscopy to ensure the synthesis of double bond double networks; finally, the rheological properties of the double-network asphalt are verified by differential scanning calorimetry; the research results will play a certain guiding role in in-depth exploration of the self-healing ability of asphalt materials and expanding the application of asphalt materials.

[0031] The purpose of the present invention is achieved through the following technical solutions:

[0032] A method for preparing double network modified asphalt comprises the following steps:

[0033] S1. Preparation of amide groups containing hydrogen bonds and Diels-Alder bonds (hereinafter referred to as DA bonds):

[0034] S1-1. Preparation of hydrogen bonds: Hydrogen bond monomers are prepared by reacting hydroxyl groups with isocyanate groups. The specific experimental process is as follows:

[0035] First, 10 mL of N-(2-hydroxyethyl)acrylamide and 15 mL of n-butyl isocyanate were added into a test tube and reacted for 1 h at a stirring rate of 250 r / min to make the reactants uniformly mixed;

[0036] Secondly, add 0.2 ml of 95% catalyst dibutyltin dilaurate solution, keep stirring at 250 r / min for 3 h, and then place the test tube in an ice bath atmosphere for reaction for 5 h;

[0037] After the reaction is completed, the product in the test tube is rinsed several times, filtered, and then dried in a 70°C forced air drying oven to obtain the desired hydrogen-bonded amide groups after the polymerization reaction;

[0038] S1-2, DA bond preparation:

[0039] 4.29 g of bismaleimide was fully dissolved in a container containing 6 mL of sugar alcohol, and reacted at a temperature of 60 ° C and a stirring rate of 250 r / min for 24 h;

[0040] The solution after the reaction was completed was poured into a mold, and placed in a 70°C forced air drying oven for drying and curing for 24 hours to obtain a monomer molecule containing a DA bond;

[0041] S2, double network asphalt cross-linking:

[0042] 44.6 g of butyl acrylate and 8.6 g of 99 wt% hydrogen-bonding molecular solution were placed in a three-necked flask. Under nitrogen protection, oxygen in the solution was removed by bubbling for 30 min. Then, the solution was heated in a 70°C water bath at 250 r / min for 5 h with mechanical uniform stirring.

[0043] After the reaction was completed, 1 mL of sugar alcohol was slowly added dropwise and reacted for 5 h. Then the temperature was lowered to 60 °C and 4.29 g of bismaleimide was added and reacted for 3 h to finally obtain a light yellow double bond prepolymer.

[0044] S3. Incorporate double bond molecules into SBS modified asphalt. The steps are as follows:

[0045] S3-1. Weigh 300 g of SBS modified asphalt, put the SBS modified asphalt into a metal container, and heat it in an oven to 170° C.;

[0046] S3-2. After the asphalt is melted, take it out and put it on a heating furnace with asbestos mesh. Keep the temperature of the asphalt at 170℃. Use a high-speed shearing machine to shear the SBS modified asphalt at 1500r / min for 10min. Use a thermometer to control the heating temperature at 170℃.

[0047] S3-3, weighing a double bond prepolymer, preheating the double bond prepolymer to 60° C. in an oven, and finally adding the preheated double bond prepolymer to the SBS modified asphalt treated in the previous step, keeping the shear rate and the asphalt temperature unchanged for 30 minutes, to obtain a double network modified asphalt; the double bond prepolymer and the SBS modified asphalt treated in the previous step are in a mass ratio of 100g:200g;

[0048] S3-4. The obtained double network modified asphalt is placed in an oven at 105°C for 2 hours to cure the SBS modified asphalt therein completely, and then a test mold is cast and the test mold is placed at room temperature for 24 hours to obtain a double network modified asphalt. The tensile strength of the asphalt after the first self-healing is 109.87% of the original, and the tensile length is 78.09%.

[0049] In the present invention:

[0050] The DA bond described in step S1 is a carbon-carbon double bond formed on the ring through an addition reaction.

[0051] Step S3 prepares a hydrogen bond-DA bond SBS modified asphalt sample required for subsequent tests, which is hereinafter represented by SBS-XY, wherein X represents the hydrogen bond content and Y represents the DA bond content, such as SBS-4-8, which represents a double network SBS modified asphalt synthesized with 4 hydrogen bonds and 8 DA bonds;

[0052] In step S3, double network asphalt is prepared according to the ratio of SBS-4-8, SBS: hydrogen bond: DA bond = 100:4:8. Double network asphalts of different ratios can be prepared according to the change of the ratio.

[0053] The present invention also relates to a double network modified asphalt, which is obtained by using the above-mentioned preparation method of the double network modified asphalt and has the following technical indicators:

[0054] Three major technical indicators of double network modified asphalt:

[0055]

[0056] Compared with the prior art, the present invention has the following advantages:

[0057] 1. A method for preparing a double network modified asphalt described in the present invention, wherein the double network crosslinking adopts a two-step process, including prepolymerization and chain extension. First, polyisocyanate and polyol are reacted to obtain a polyurethane prepolymer containing terminal isocyanate, and then the polyurethane prepolymer is subjected to a chain extension reaction with a diol or a diamine to finally obtain a complete polyurethane product.

[0058] The present invention uses a two-step method to perform network crosslinking of hydrogen bonds and DA bonds: first, a free radical polymerization reaction of hydrogen bond monomer molecules and olefins of butyl acrylate is used, and then a crosslinking reaction is performed with a sugar alcohol containing a furan group to obtain a polymer, and finally maleimide groups (BMI) of different proportions are added to the polymer to form DA bonds, thereby forming linear copolymers of hydrogen bonds-DA bonds with different crosslinking proportions. The two-step method has the advantages of easy reaction control, regular product structure, good mechanical properties, good repeatability, etc. It is not only commonly used in industry to prepare high-performance polyurethanes, but also widely used in structural design in the research field.

[0059] 2. The double network modified asphalt described in the present invention, when subjected to external force, the hydrogen bond will be broken first as a sacrificial bond to dissipate energy, thereby improving the toughness of the asphalt; when the external force is eliminated, the DA bond will restore the asphalt to its original shape due to its higher bond energy. At the same time, at a certain temperature, the DA bond will undergo a reversible chemical reaction, and the broken DA bond and hydrogen bond will recombine to form bonds, thereby achieving self-healing of the asphalt material performance. Under the coordination of this reversible double network structure, the tensile strength of the asphalt after the first self-healing is 109.87% of the original, and the tensile length is 78.09%; the tensile strength of the asphalt not under the double network structure after the first self-healing is only 66.1% of the original, and the tensile length is 69.86%. Therefore, asphalt under the double network structure can help the asphalt to self-heal, thereby extending the service life of the asphalt. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0061] Figure 1 This is a process diagram for preparing hydrogen bond monomer molecules in Example 1 of the present invention;

[0062] Figure 2 This is a process diagram for preparing DA bond monomer molecules in Example 1 of the present invention;

[0063] Figure 3 is a linear polymerization route diagram containing hydrogen bonds and DA bonds in Example 1 of the present invention;

[0064] Figure 4 The dual network asphalt polymerization route map in Example 1 of the present invention;

[0065] Figure 5 This is an infrared spectrum of the SBS modified asphalt in Example 1 of the present invention under double network conditions;

[0066] Figure 6 This is an infrared spectrum of the SBS modified asphalt in Example 1 of the present invention under double network conditions;

[0067] Figure 7 It is the asphalt tensile curve diagram at different time and temperature in Example 1 of the present invention;

[0068] Figure 8 This is the DSC curve of SBS modified asphalt under the double network in Example 1 of the present invention. DETAILED DESCRIPTION

[0069] The following embodiments are used to provide a detailed and complete description of the present invention so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention, but are not used to limit the scope of the present invention.

[0070] The raw materials used in the following examples can all be purchased commercially:

[0071] Embodiment 1:

[0072] A method for preparing double-network modified asphalt comprises the following steps:

[0073] Preparation of S1, hydrogen bonds and DA bonds:

[0074] S1-1. Hydrogen bond preparation: Hydrogen bond monomers are prepared by reacting hydroxyl groups with isocyanate groups. The specific experimental process is as follows:

[0075] First, add 10 mL of N-(2-hydroxyethyl)acrylamide and 15 mL of n-butyl isocyanate into a test tube and stir continuously to mix the reactants evenly;

[0076] Then, add a trace amount of catalyst dibutyltin dilaurate solution, keep stirring rapidly, and then place the test tube in an ice bath atmosphere and react for 5 hours;

[0077] After the reaction is completed, the product in the test tube is rinsed several times, filtered, and then dried in a 70°C forced air drying oven to obtain the small molecular monomer containing hydrogen bonds required after the polymerization reaction;

[0078] S1-2, DA bond preparation:

[0079] 4.29 g of bismaleimide was fully dissolved in a container containing 6 mL of sugar alcohol, and reacted at a temperature of 60 ° C and a stirring rate of 250 r / min for 24 h;

[0080] The solution after the reaction was completed was poured into a mold, and placed in a 70°C forced air drying oven for drying and curing for 24 hours to obtain a monomer molecule containing a DA bond;

[0081] S2, dual network cross-linking:

[0082] Put butyl acrylate and hydrogen-bonded molecular solution into a three-necked flask, and remove oxygen from the solution by bubbling for 30 minutes under nitrogen protection, and then heat in a 70°C water bath at 250 r / min for 5 hours with mechanical uniform stirring;

[0083] After the reaction was completed, 1 mL of sugar alcohol was slowly added dropwise to react for 5 h, and then the temperature was lowered to 60 °C and bismaleimide was added to react for 3 h, finally obtaining a light yellow double bond prepolymer;

[0084] S3. Incorporate double bond molecules into SBS modified asphalt. The steps are as follows:

[0085] S3-1. Weigh SBS modified asphalt, put the SBS modified asphalt into a metal container, and heat it in an oven to 170°C;

[0086] S3-2. After the asphalt is melted, take it out and put it on a heating furnace with asbestos mesh. Keep the temperature of the asphalt at 170℃. Use a high-speed shearing machine to shear the SBS modified asphalt at high speed. Use a thermometer to control the heating temperature.

[0087] S3-3, shear the SBS modified asphalt at 170℃ and 1500r / min for 10min; weigh a certain amount of prepolymer, preheat the prepolymer to 60℃ in an oven, and finally add the preheated prepolymer to the asphalt, keep the shear rate and asphalt temperature unchanged and shear for 30min, and the double network modified asphalt can be obtained;

[0088] S3-4. Place the obtained double network modified asphalt in an oven at 105°C for 2 hours to allow the SBS modified asphalt to completely solidify. Then, cast a test mold and place the test mold at room temperature for 24 hours to obtain a double network modified asphalt.

[0089] Experimental example

[0090] 1. Experiments using the double network modified asphalt prepared in Example 1

[0091] 2. Materials and methods

[0092] 2.1 Raw materials

[0093] 2.1.1 Asphalt materials

[0094] The main research object is SBS modified asphalt, model IC. Following the test method in the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011), the performance indicators of the selected asphalt samples were tested. The specific test results are shown in Table 1:

[0095] Table 1 Technical indicators and test results of SBS modified asphalt

[0096]

[0097] 2.1.2 Dual Network Materials

[0098] The hydrogen bond and DA bond synthesis reagents used in this application are shown in Table 2 below:

[0099] Table 2 Preparation of dual network materials

[0100]

[0101]

[0102] 2.2 Preparation and synthesis of SBS modified asphalt double network:

[0103] In order to obtain hydrogen bond-DA bond double network SBS modified asphalt, hydrogen bond and DA bond are synthesized in this section, and then the two are cross-linked with SBS modified asphalt. The hydrogen bond-DA bond SBS modified asphalt sample required for subsequent experiments is prepared, which is denoted by SBS-XY in the following text, where X represents the hydrogen bond content and Y represents the DA bond content, such as SBS-4-8, which represents a double network SBS modified asphalt synthesized with 4 hydrogen bonds and 8 DA bonds.

[0104] 2.2.1 Hydrogen bond preparation:

[0105] Hydrogen bond monomers were prepared by reacting hydroxyl groups with isocyanate groups. The specific experimental process was as follows: first, 10 mL of N-(2-hydroxyethyl) acrylamide and 15 mL of n-butyl isocyanate were added to a test tube and stirred continuously to mix the reactants evenly; secondly, a trace amount of catalyst dibutyltin dilaurate solution was added and stirred rapidly, and then the test tube was placed in an ice bath atmosphere and reacted for 5 hours; after the reaction was completed, the catalyst of the product was rinsed and filtered out several times, and then dried in a 70°C forced air drying oven to obtain the small molecular monomer containing hydrogen bonds required after the polymerization reaction, and its structure is as shown below: Figure 1 As shown;

[0106] Figure 1 Preparation of hydrogen-bonded monomer molecules;

[0107] 2.2.2DA bond preparation:

[0108] 4.29 g of BMI was fully dissolved in a 6 mL sugar alcohol container and reacted at 60°C and a stirring rate of 250 r / min for 24 h. The reaction solution was poured into a mold and placed in a 70°C forced air drying oven for drying and curing for 24 h to obtain a monomer molecule containing a DA bond. The synthesis route is as follows: Figure 2 As shown;

[0109] Figure 2 Preparation of DA bond monomer molecules;

[0110] 2.2.3 Dual network cross-linking:

[0111] The two-step method includes prepolymerization and chain extension. First, polyisocyanate and polyol are reacted to obtain a polyurethane prepolymer containing terminal isocyanate, and then the polyurethane prepolymer is subjected to chain extension reaction with diol or diamine to finally obtain a complete polyurethane product. The two-step method has the advantages of easy reaction control, regular product structure, good mechanical properties, and good repeatability. It is not only commonly used in industry to prepare high-performance polyurethane, but also widely used in structural design in the research field.

[0112] The present application uses a two-step method to perform network crosslinking of hydrogen bonds and DA bonds: first, a free radical polymerization reaction of hydrogen bond monomer molecules and olefins of butyl acrylate is used, and then a crosslinking reaction is performed with a sugar alcohol containing a furan group to obtain a polymer, and finally different proportions of maleimide groups (BMI) are added to the polymer to form DA bonds, thereby forming linear copolymers of hydrogen bonds-DA bonds with different crosslinking ratios, such as Figure 3 As shown;

[0113] The specific implementation process is as follows: butyl acrylate and hydrogen bond molecule solution are placed in a three-necked flask, and under nitrogen protection, the oxygen in the solution is removed by bubbling for 30 minutes, and then heated in a 70°C water bath at 250r / min for 5 hours with mechanical uniform stirring; after the reaction is completed, sugar alcohol is slowly dripped in for 5 hours, and then the temperature is lowered to 60°C and BMI is added for 3 hours to finally obtain the light yellow double bond prepolymer required for the research;

[0114] Figure 3 Linear polymerization routes containing hydrogen bonds and DA bonds;

[0115] According to research, the steps to incorporate double bond molecules into SBS modified asphalt are as follows:

[0116] (1) Weigh a certain amount of SBS modified asphalt, put the SBS modified asphalt into a metal container, and heat it in an oven to 170°C;

[0117] (2) After the asphalt is melted, take it out and place it on a heating furnace with an asbestos mesh. Keep the temperature of the asphalt at 170°C. Use a high-speed shearing machine to shear the SBS modified asphalt at high speed. Use a thermometer to control the heating temperature.

[0118] (3) SBS modified asphalt is sheared at 170°C and 1500 r / min for 10 min; a certain amount of prepolymer is weighed, and the prepolymer is preheated to 60°C in an oven, and finally the preheated prepolymer is added to the asphalt, and the shear rate and asphalt temperature are kept constant for shearing for 30 min, thereby obtaining a double network modified asphalt;

[0119] (4) The obtained double network modified asphalt was placed in an oven at 105°C for 2 hours to allow the SBS modified asphalt to completely solidify, and then a test mold was cast and placed at room temperature for 24 hours.

[0120] Flowchart as Figure 4 As shown;

[0121] Figure 4 Dual network asphalt polymerization route.

[0122] 2.3 Test method:

[0123] 2.3.1 Infrared spectrum test:

[0124] Infrared spectroscopy (IR) is often used to analyze the chemical structure and composition of asphalt. When infrared radiation of different wavelengths is irradiated on the asphalt sample, the asphalt sample will selectively absorb certain wavelengths of infrared light to form an absorption spectrum. Infrared spectroscopy (IR) analysis allows the identification and differentiation of different functional groups and components in the asphalt sample at the molecular level. In this application, the inventor selected the Nicolet iS 50 infrared spectrometer from Thermo Fisher Scientific. When performing the IR test, the aged asphalt sample is first heated to a liquid state, then dripped into a pre-prepared mold and allowed to cool to room temperature. After cooling, the sample is placed in a spectrometer for analysis. The infrared spectrum range of the test is set to 4000cm -1 Up to 650cm -1 , 64 scans were performed, each with a resolution of 4 cm -1 .

[0125] 2.3.2 Force ductility test:

[0126] The Force Ductility Test (FDT) can be used to evaluate some mechanical properties of asphalt. The Force Ductility Test can measure mechanical indicators such as the maximum stress, yield stress and fracture stress of asphalts with different properties. Through this method, the changes in the mechanical properties of SBS modified asphalt under different double bonds can be intuitively seen.

[0127] 2.3.3 Differential Scanning Calorimeter

[0128] Differential Scanning Calorimetry (DSC) tests were performed using a Q2000 modulated differential scanning calorimeter (TA Company, USA). After eliminating the thermal history, all samples 5-10 mg were placed in a N2 atmosphere with an air flow rate of 50 mL / min and a heating and cooling rate of 10°C / min.

[0129] 3 Results and discussion

[0130] 3.1 Infrared spectrum test analysis

[0131] Infrared spectroscopy (IR) can understand the functional groups in SBS modified asphalt at the molecular level, and can judge whether the double bond crosslinking of SBS modified asphalt is effective by the changes before and after the functional groups. This section conducts infrared spectroscopy tests on SBS modified asphalt samples of SBS-0-0, SBS-0-8, SBS-4-0 and SBS-4-8. In order to detect whether the DA bond is formed in SBS modified asphalt, this application uses SBS-0-0 and SBS-0-8 samples to represent the samples before and after the DA bond crosslinking, and tests them with an infrared spectrometer. The test results are as follows: Figure 5 shown.

[0132] Depend on Figure 5 It can be seen that due to the addition of polymer chains containing DA bonds to SBS-0-8, SBS-0-8 has multiple absorption peaks, including 1491cm -1 、844cm -1 、1700cm -1 and 1775cm -1 Absorption peak at 1700cm -1 and 1775cm -1 The absorption peak at is the characteristic peak of DA bond, such as Figure 5 (a)), where the -1 The absorption peak of BMI is the stretching vibration peak of C=C on the benzene ring; and at 844cm -1 The absorption peak at is the C=C bending vibration peak in the BMI maleimide ring, such as Figure 5 (b)), which confirms that the DA bond is a successful cross-linking at the molecular level.

[0133] Figure 5 Infrared spectrum of SBS modified asphalt under double network conditions;

[0134] Hydrogen bond is an important non-covalent bond between molecules. In infrared spectroscopy, the presence of hydrogen bond usually affects the vibration frequency of certain functional groups in the molecule, thereby changing the position and shape of its functional group absorption peak. In order to detect whether hydrogen bonds are formed in SBS modified asphalt, this application uses SBS-0-8 and SBS-4-8 samples to represent the samples before and after hydrogen bond crosslinking, and tests them with an infrared spectrometer. The test results are as follows: Figure 6 As shown. Figure 6 (a) shown, 3324cm -1 The NH stretching vibration peak at the amide bond is the restricted amino group. Figure 6 (b) It can be seen that 1720cm -1The peak at 1670 cm-1 is the unrestricted carbonyl stretching vibration peak on the amide bond. -1 It is the NH bending vibration peak belonging to the restricted amino group on the amide bond. At the same time, by analyzing the peak characteristics of SBS-0-8 and SBS-4-8 samples, it can be found that the peak of SBS-4-8 will move toward the low wave number direction as a whole relative to SBS-0-8. This may be due to the influence of the hydrogen bond effect. The formation of hydrogen bonds will cause the stretching vibration peak to move toward the low wave number direction. The formation of hydrogen bonds reduces the bond force constant between hydrogen atoms and the atoms they are linked to, thereby reducing the vibration frequency. The presence of hydrogen bonds can also increase the absorption intensity of certain vibration modes, resulting in a wider absorption peak. These changes reflect the influence of hydrogen bonds on the molecular vibration state, thereby determining that hydrogen bond polymer chains have been successfully integrated into the SBS modified asphalt to form hydrogen bonds.

[0135] Figure 6 Infrared spectrum of SBS modified asphalt under double network conditions;

[0136] 3.2 Digital ductility test analysis

[0137] In order to study the synthetic effect of the self-healing performance of double network asphalt on the macro scale, this section uses a digital force-ductility instrument to explore the changes in mechanical properties of SBS modified asphalt samples with different double bond contents before and after self-healing. Using the data processing PrPrAusw provided by the digital force-ductility instrument, multi-parameter data statistics are performed on SBS modified asphalt samples with different double bond contents, and finally a multi-parameter data analysis chart is formed. At the same time, the maximum tensile stress, tensile length, and tensile modulus of SBS modified asphalt before and after self-healing are analyzed to reveal the behavioral changes of different double bond contents on the mechanical properties of SBS modified asphalt, thereby verifying that the double bond content at the macro scale has been successfully cross-linked in SBS modified asphalt. When conducting force-ductility tensile tests, due to the influence of factors such as sample preparation and instrument force measurement errors, the maximum tensile stress and tensile length measured may have different degrees of deviation. In order to solve this kind of problem, three parallel tests were conducted on SBS modified asphalt of different samples using the specification "JTG E20-2011", and the average of the three measured results was taken, and the final results were plotted using Origin software. After processing, the test can effectively solve the consequences caused by instrument errors and other operations, thereby improving the accuracy of the asphalt tensile test of SBS modified asphalt. In this section, all SBS modified asphalt samples were tested in parallel three times. This study analyzes how the mechanical properties of SBS modified asphalt change under self-healing conditions at different temperatures and different times after adding different double bond contents. Figure 7 The effect of different double bond contents on SBS modified asphalt is described in.

[0138] Figure 7Asphalt tensile curves at different time and temperature ((a) untreated; (b) cured at 30℃ for 12h; (c) cured at 60℃ for 12h; (d) cured at 60℃ for 24h);

[0139] Depend on Figure 7 (a) It can be seen that when the SBS modified asphalt samples with different dosages were stretched before being cut, the maximum loading stress of SBS-0-0 was the largest, followed by SBS-4-8, SBS4-0, and finally SBS-0-8. This may be because when the SBS modified asphalt was stretched, the hydrogen bond acted as a sacrificial bond, offsetting part of the energy dissipation caused by stretching, thereby increasing the maximum tensile stress of the SBS modified asphalt sample containing hydrogen bonds. Comparing the samples SBS-0-8 and SBS-4-0, it can be seen that the maximum tensile stress of SBS-4-0 is relatively higher due to the incorporation of polymer chains with hydrogen bonds. This may also be because the DA bond needs to react at 50-60℃ to activate its own self-healing properties, resulting in the inability to self-heal asphalt at room temperature, making the tensile stress of SBS-0-8 lower than that of SBS-4-0. However, the maximum tensile stress of SBS-4-8 is higher than that of SBS-4-0. It can be found that under the coordination of double bonds, the maximum tensile stress of SBS modified asphalt is not much different from that of SBS-0-0. Compared with the single bond energy effect, the double mechanism effect is better. With the increase of tensile length, it can be clearly observed that SBS-4-0 has the best tensile effect, followed by SBS-0-0, SBS-0-8, and SBS-4-8. This may be due to the presence of hard segments and soft segments in polyurethane. For the polymer chains containing hydrogen bonds formed by the connection of alcohols and isocyanates, they belong to the soft segments, and the molecular chains are relatively soft and easy to stretch. When the polymer chains containing hydrogen bonds are added to SBS modified asphalt, the SBS modified asphalt samples will become softer, and the tensile length will be relatively longer than that of the SBS-0-0 samples without hydrogen bonds. Similarly, for the DA bond type, the polymer chains formed by chain extension with isocyanate belong to the hard segments, and the molecular chains are relatively easy to stretch and break. When polymer chains containing DA bonds are added to SBS modified asphalt, it can be seen that the breaking lengths of SBS-0-8 and SBS-0-0 are not much different, but when SBS-4-8 has both hydrogen bonded polymer chains and DA bonded polymer chains, the maximum tensile length of SBS-4-8 is significantly reduced. This may be because SBS modified asphalt becomes easy to break under the action of the double network. In this section, only SBS modified asphalts with different double bond contents are compared and verified horizontally to confirm that hydrogen bonds and DA bonds are successfully integrated into the cross-linked SBS modified asphalt.

[0140] Since the self-healing effect of DA bonds requires a reversible reaction at 50-60°C, the self-healing purpose is achieved through the breaking and overlapping of bonds. Figure 7 (b) and Figure 7 (c) compares the stress-strain distribution trends of SBS modified asphalt samples at different temperatures. Figure 7 It can be clearly observed in (b) that after curing at 30°C for 12 hours, the tensile length of SBS-0-0 is 465.6, and the tensile lengths of SBS-0-8, SBS-4-0 and SBS-4-8 are 445.7, 335.3 and 273.8 respectively. At this time, the tensile properties of SBS modified asphalt without double bonds are the best. Figure 7 In (c), it can be observed that after curing at 60°C for 12h, the tensile length of SBS-0-0 is 338.9, and the tensile lengths of SBS-0-8, SBS-4-0 and SBS-4-8 are 509.62, 331.9 and 299.4 respectively. The results obtained from the two groups of samples cured at different temperatures for the same time show that the tensile length of SBS-0-0 decreased by 4.3%, the tensile length of SBS-0-8 increased by 14.3%, the tensile length of SBS-4-0 decreased by 1%, and the tensile length of SBS-4-8 increased by 9.3%. This phenomenon shows that when SBS modified asphalt contains hydrogen bonds, the sensitivity of SBS modified asphalt to changes in mechanical properties caused by temperature changes will be weakened; when SBS modified asphalt contains DA bonds, a thermally reversible reaction occurs inside the SBS modified asphalt, and the tensile properties of the SBS modified asphalt are improved; when SBS modified asphalt contains hydrogen bonds and DA bonds, on the one hand, the hydrogen bonds reduce the sensitivity of SBS modified asphalt to temperature, and on the other hand, the reversible reaction of DA bonds improves the tensile properties of SBS modified asphalt, ultimately resulting in the tensile performance improvement effect not being as good as that of SBS modified asphalt after DA bonds are incorporated.

[0141] 3.3 Differential scanning calorimeter test analysis:

[0142] Differential Scanning Calorimetry (DSC) is an instrument that measures the power and temperature relationship between a sample and a reference under temperature control. The reference will not undergo phase changes within the test temperature range, while the sample will undergo heat absorption changes inside as the temperature changes. The difference in heat absorption will present a curve peak on the DSC curve. The area of ​​the peak can be calculated based on the position of the peak and the baseline, which is the heat absorbed by the sample. With different temperatures, the phase substances in asphalt will change in different proportions, thus showing certain differences in mechanical properties. Asphalt is a mixture, and its components will undergo solid and liquid aggregation states with temperature. At the same temperature, different components of asphalt will show different phases, but the molecular forces between phases are different, so that the changes in the aggregation state of asphalt will affect its physical properties to a certain extent. Within a certain temperature range, if the various components of asphalt undergo more aggregation states, the macroscopic properties of asphalt will change significantly, resulting in poor temperature stability. If the above temperature range is within the service temperature range of asphalt pavement, it will affect the normal service of asphalt pavement. When asphalt undergoes phase changes, the more heat absorbed, the worse the temperature stability. Therefore, DSC test can be used to test the temperature change of asphalt, so as to analyze and characterize the cross-linking results of double network asphalt in rheological mechanics. In this section, DSC test is carried out on SBS modified asphalt samples with four different double bond contents, and DSC spectrum is plotted with temperature as the horizontal axis and heat flow rate as the vertical axis. The test results are shown in the figure. Figure 8 By analyzing the changes of samples with temperature in the DSC graph, the temperature stability of four types of SBS modified asphalt was analyzed.

[0143] There are many methods for selecting the glass transition temperature (Tg). In this section, the midpoint of the first step in the DSC curve is used as Tg. Figure 7 It can be seen that the glass transition temperature of SBS-0-0 is 42.9°C, while the glass transition temperatures of SBS-0-8, SBS-4-0 and SBS-4-8 with different double bonds are 42.3°C, 47.7°C and 41.9°C respectively. Except that the glass transition temperature of SBS-4-0 is greater than that of SBS-0-0, the glass transition temperatures of the other two asphalts are lower than that of SBS-0-0. This is because the addition of hydrogen bonds will increase the intermolecular forces, making the molecular chains more stable and increasing the rigidity of the molecular chains. The greater the rigidity of the molecular chains, the higher the glass transition temperature. At the same time, the glass transition temperature results show that the glass transition temperatures of the four asphalts are SBS-4-0>SBS-0-0>SBS-0-8>SBS-4-8, which is consistent with the tensile length arrangement results in the force-ductility test under 5°C conditions. From Figure 8It can be seen that the endothermic peak positions of SBS-0-0 and SBS-4-8 are the same, but the absorbed heat is different, and the DSC curves of SBS-0-8, SBS-4-0 and SBS-0-0 are obviously different, and the curves of the two are relatively bumpy. In general, the DSC curves of the four asphalts are different, and the endothermic peaks are small. The total absorbed heat of SBS-0-0 is 0.07 J / g, and the total absorbed heat of SBS-0-8, SBS-4-0 and SBS-4-8 are 1.17 J / g, 1.31 J / g, and 0.04 J / g, respectively. The smaller the absorbed heat, the more stable the properties of the asphalt.

[0144] Figure 8 DSC curve of SBS modified asphalt under double network;

[0145] according to Figure 8 The DSC related data of SBS modified asphalt under the dual network were analyzed, and all the data in the figure were retained to two decimal places. The specific results are shown in Table 3.

[0146] Table 3 DSC indexes of double network SBS modified asphalt

[0147]

[0148] From the results in Table 3, it can be concluded that when the molecules containing hydrogen bonds and DA bonds are added to SBS modified asphalt alone, SBS modified asphalt undergoes different degrees of change, but when hydrogen bonds and DA bond polymers are added to SBS modified asphalt at the same time, the heat absorption is reduced by 0.03 J / g relative to SBS modified asphalt. This shows that among the four types of samples, SBS-4-8 has the best temperature stability and the best physical properties, which is consistent with the conclusion that the tensile stress of SBS-4-8 is the best physical property obtained by the force-ductility test.

[0149] When molecules containing hydrogen bonds and DA bonds are added to SBS modified asphalt, the temperature stability of the asphalt in its DSC curve will be different from that of SBS modified asphalt to a certain extent. This is because hydrogen bond and DA bond molecules are both small molecular compounds. The molecules are small, the interaction force between molecules is small, and the molecular chains are not arranged tightly. When the temperature changes, the molecular forces will change greatly, and the molecular chain segments will move, which is manifested as poor temperature stability at the macro level. Since SBS modified asphalt is added with SBS modifier, and the molecular weight of SBS modifier is large, SBS modified asphalt belongs to a polymer mixture, the molecules are entangled with each other, and there is a large interaction force between molecules. The molecules are arranged relatively tightly and are not easy to move relative to each other, which is manifested as good temperature stability at the macro level. This series of results shows that hydrogen bonds and DA bonds will undergo endothermic reactions with temperature changes, and also shows that hydrogen bonds and DA bonds have successfully cross-linked with SBS modified asphalt from the perspective of molecular movement. When hydrogen bonds and DA bonds are added to SBS modified asphalt at the same time, the temperature stability of SBS modified asphalt is further reduced. This may be because the molecules of hydrogen bonds and DA bonds are mixed and cross-linked to form macromolecules. After being added to SBS modified asphalt, the content of macromolecule components is relatively increased, and the content of small molecules is relatively reduced. At the same time, some small asphalt molecules in the SBS modified asphalt components may also be adsorbed on the macromolecular polymers formed by hydrogen bonds and DA bonds due to molecular diffusion, thereby reducing the number of small molecules in SBS modified asphalt. In general, an increase in molecular weight will increase the force between molecules. The addition of double bonds, to a certain extent, limits the relative movement of molecules, reduces the fluidity of molecular bonds, improves the temperature stability of asphalt, and improves the physical properties of asphalt. This phenomenon shows that compared with the effect of a single bond energy, the physical properties of SBS modified asphalt are improved under the "coordination" of double bonds, thereby verifying that double bonds are successfully cross-linked in SBS modified asphalt.

[0150] 4. Conclusion:

[0151] This application synthesized and prepared the hydrogen bond-DA bond double network SBS modified asphalt, and verified the double bond synthesis by infrared spectroscopy test, further conducted tensile and differential thermal scanning tests on the SBS modified asphalt in different states, and comprehensively analyzed the performance of the hydrogen bond-DA bond double network SBS modified asphalt, which is summarized as follows:

[0152] (1) By conducting infrared spectroscopy tests on double-network SBS modified asphalt, it was found that the spectrum of SBS-0-8 showed obvious characteristic peaks of DA bonds compared with that of SBS-0-0; the spectrum of SBS-4-8 showed obvious characteristic peaks of amide hydrogen bonds compared with that of SBS-0-8. This shows that the double bond of SBS-4-8 is successfully integrated into the SBS modified asphalt.

[0153] (2) Through the asphalt tensile test analysis of the double network SBS modified asphalt, the tensile stress value of SBS-0-0 is the largest when it is untreated, which is 72.04, followed by SBS-4-8, which is 71.3. When the asphalt is cut and self-healed at different temperatures for different time periods, and then stretched, the tensile stress of SBS-4-8 is the largest, indicating that the double bonds will improve the self-healing ability of asphalt through mutual coordination, thereby improving the mechanical properties of asphalt.

[0154] (3) In the differential thermal scanning diagram of asphalt, the total absorption peak energy value of SBS-0-0 is 0.07 J / g, while that of SBS-4-8 is 0.04 J / g, indicating that the presence of double bonds will restrict the flow of asphalt molecules, improve the physical properties of asphalt, reduce the degree of damage to asphalt, and thus achieve a self-healing effect.

[0155] (4) The test results of asphalt stretching and differential thermal scanning are consistent, which strongly proves that the double bonds have been successfully integrated into the asphalt. At the same time, the test results show that SBS-4-8 has certain advantages in physical properties compared with SBS-0-0.

[0156] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing double network modified asphalt, characterized in that: The steps include: S1. Preparation of amide groups containing hydrogen bonds and Diels-Alder bonds: S1-1. Preparation of hydrogen bonds: Hydrogen bond monomers are prepared by reacting hydroxyl groups with isocyanate groups. The specific experimental process is as follows: First, 10 mL of N-(2-hydroxyethyl)acrylamide and 15 mL of n-butyl isocyanate were added into a test tube and reacted for 1 h at a stirring rate of 250 r / min to make the reactants uniformly mixed; Secondly, add 0.2 ml of 95% catalyst dibutyltin dilaurate solution, keep stirring at 250 r / min for 3 h, and then place the test tube in an ice bath atmosphere for reaction for 5 h; After the reaction is completed, the product in the test tube is rinsed several times, filtered, and then dried in a 70°C forced air drying oven to obtain the desired hydrogen-bonded amide groups after the polymerization reaction; S1-2, DA bond preparation: 4.29 g of bismaleimide was fully dissolved in a container containing 6 mL of sugar alcohol, and reacted at a temperature of 60 ° C and a stirring rate of 250 r / min for 24 h; The solution after the reaction was completed was poured into a mold, and placed in a 70°C forced air drying oven for drying and curing for 24 hours to obtain a monomer molecule containing a DA bond; S2, double network asphalt cross-linking: 44.6 g of butyl acrylate and 8.6 g of 99 wt% hydrogen-bonding molecular solution were placed in a three-necked flask. Under nitrogen protection, oxygen in the solution was removed by bubbling for 30 min. Then, the solution was heated in a 70°C water bath at 250 r / min for 5 h with mechanical uniform stirring. After the reaction was completed, 1 mL of sugar alcohol was slowly added dropwise and reacted for 5 h. Then the temperature was lowered to 60 °C and 4.29 g of bismaleimide was added and reacted for 3 h to finally obtain a light yellow double bond prepolymer. S3. Incorporate double bond molecules into SBS modified asphalt. The steps are as follows: S3-1. Weigh 300 g of SBS modified asphalt, put the SBS modified asphalt into a metal container, and heat it in an oven to 170° C.; S3-2. After the asphalt is melted, take it out and put it on a heating furnace with asbestos mesh. Keep the temperature of the asphalt at 170℃. Use a high-speed shearing machine to shear the SBS modified asphalt at 1500r / min for 10min. Use a thermometer to control the heating temperature at 170℃. S3-3, weighing a double bond prepolymer, preheating the double bond prepolymer to 60° C. in an oven, and finally adding the preheated double bond prepolymer to the SBS modified asphalt treated in the previous step, keeping the shear rate and the asphalt temperature unchanged for 30 minutes, to obtain a double network modified asphalt; the double bond prepolymer and the SBS modified asphalt treated in the previous step are in a mass ratio of 100g:200g; S3-4. The obtained double network modified asphalt is placed in an oven at 105°C for 2 hours to cure the SBS modified asphalt therein completely, and then a test mold is cast and the test mold is placed at room temperature for 24 hours to obtain a double network modified asphalt. The tensile strength of the asphalt after the first self-healing is 109.87% of the original, and the tensile length is 78.09%.

2. The method for preparing a double network modified asphalt according to claim 1, characterized in that: The DA bond described in step S1 is a carbon-carbon double bond formed on the ring through an addition reaction.

3. A double network modified asphalt, characterized in that: The double network modified asphalt prepared by the method according to claim 1 or 2 has the following technical indicators: The tensile strength of the asphalt after the first self-healing is 109.87% of the original value, and the tensile length is 78.09%.

Citation Information

Cited By

  • Preparation method of double-network toughening elastomer based on hydrogen bond and DA crosslinking

    CN120349538A

  • High-viscosity and high-toughness self-repairing modified asphalt based on dual dynamic cross-linked network structure as well as preparation method and application of high-viscosity and high-toughness self-repairing modified asphalt

    CN120349659A

  • Multi-time self-repairing modified asphalt based on photo-thermal filler and dynamic hydrogen bond material and preparation method of multi-time self-repairing modified asphalt

    CN121271270A